Dietary supplements in polycystic ovary syndrome–current evidence - Han, Ya; Hou, Ye; Han, Qimao; Yuan, Xingxing; Chen, Lu (Frontiers in Endocrinology, 2024)
Polycystic ovary syndrome (PCOS) is the most prevalent endocrine disorder in women of reproductive age, and presents a significant challenge to the global population. This review provides comprehensive evidence of interventions, including food and dietary supplements, aimed at reversing PCOS and improving fertility outcomes. Various dietary supplements are known to cause metabolic changes and hormonal regulation and have a potential impact on increasing pregnancy rates. Although some biochemical alterations have been observed, these metabolic changes do not directly reverse the disorder. Moreover, the lack of sufficient evidence does not convince clinicians to standardize dietary supplements as alternatives to medical or pharmacological interventions. This calls for a study of women with PCOS taking dietary supplements. In addition, unbiased studies of combinations of treatment options for supplements, including large cohort clinical trials, will lead to evidence-based medicine.